Integration of a Kampo Medicine, Nijutsuto, and Western Medical Treatment in the Treatment of Long-term Frozen Shoulder Refractory to Western Medical Treatment: A Case Series. (April 2015) - Arai, Young-Chang; Shimo, Kazuhiro; Inoue, Masayuki; Sakurai, Hiroki; Ohmichi, Yusuke; Matsubara, Takako; Nishihara, Makoto; Kawai, Takashi; Ikemoto, Tatsunori; Inoue, Shinsuke
Objective: Frozen shoulder is a common disorder in general orthopedic practice, characterized by spontaneous onset of pain in the shoulder and accompanied by limitation of glenohumeral movement. Treatments for frozen shoulder include shoulder exercise, manual therapy, corticosteroid injection, manipulation under anesthesia, and arthroscopic capsular release. Several patients suffer from some degree of pain and range of motion limitation for up to 10 years even when these treatments are applied. Kampo, a traditional Japanese herbal medicine based on traditional Chinese herbal medicine, has been used for the treatment of pain in Japan. Nijutsuto has been a Kampo formula used to effectively treat frozen shoulder. Methods: Thirteen patients suffering from long-term frozen shoulder refractory to Western medical treatment were administered Nijututo . Results: Almost all patients experienced sound pain relief after Nijutsuto admnistration. There were no severe side effects reported. Conclusion: Nijutsuto combined with an exercise program improved pain intensity in 13 patients with long-term frozen shoulder.